A Note on Bias in the Almon Distributed Lag Estimator - Terasvirta, Timo (Econometrica, 1976)
IN A RECENT PAPER Cargill and Meyer [1] use Monte Carlo simulations to examine the behavior of some distributed lag estimators when the lag structure is misspecified. The authors hold that it is not easy to compare the Almon polynomial lag method and OLS analytically if the restrictions imposed by the Almon procedure are not correct. It is our intention to derive analytical expressions for the bias in the Almon estimator. We postulate a linear distributed lag model